Tariffs, Optimal Taxes, and Collection Costs - Mihaljek, Dubravko (IMF Working Papers; Working Paper ;, 1992)
This paper studies an optimal tax problem for a small open economy where collecting taxes is costly. It is shown that, in the presence of collection costs modeled as an increasing function of the tax rate: (a) the standard rules of optimal commodity taxation (the Ramsey, the inverse elasticity, the Corlett-Hague rules) may no longer be valid; (b) tariffs may replace domestic taxes as a second-best revenue-raising device; and (c) the optimal tariff/tax structure may be uniform rather than differentiated.